2013
DOI: 10.1177/0269215513488122
|View full text |Cite
|
Sign up to set email alerts
|

Clinical tools that measure sitting posture, seated postural control or functional abilities in children with motor impairments: a systematic review

Abstract: Although a number of tools are available, evidence supporting their use for seating interventions is limited, as is the evidence supporting the strength of their measurement properties. Few tools address participation, environmental factors or the child's and family's perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 93 publications
(280 reference statements)
0
18
0
Order By: Relevance
“…1,25 We chose to use the SPCM and SAS because there are validity and reliability studies for these assessment tools, and they have face validity. 10,18,26 The results of this study showed that there is a very obvious need for postural support for seating in children with CP, since there was a significant difference in most In the present study, GMFCS Level 3, 4, and 5 children were included because the children in these levels require seating systems more, and it has been reported numerous times that as the level increases, their need for seating systems also increases. 11,17 It was surprising (because it contradicts with the literature) to see that there were differences among groups in terms of all SPCM values in both all children ungrouped as well as grouped, and paired comparisons showed no difference between seating groups except in Level 4 children.…”
Section: Discussionmentioning
confidence: 78%
“…1,25 We chose to use the SPCM and SAS because there are validity and reliability studies for these assessment tools, and they have face validity. 10,18,26 The results of this study showed that there is a very obvious need for postural support for seating in children with CP, since there was a significant difference in most In the present study, GMFCS Level 3, 4, and 5 children were included because the children in these levels require seating systems more, and it has been reported numerous times that as the level increases, their need for seating systems also increases. 11,17 It was surprising (because it contradicts with the literature) to see that there were differences among groups in terms of all SPCM values in both all children ungrouped as well as grouped, and paired comparisons showed no difference between seating groups except in Level 4 children.…”
Section: Discussionmentioning
confidence: 78%
“…The reviews selected from this process included seating interventions [8], power mobility interventions [9], motor interventions [10], and treadmill training [11], as well as reviews of measurement tools suitable for children with CP [12], children using seating interventions [13], and children using power mobility [14]. The additional tools were only included based on agreement of the two reviewers if at least one study evidencing psychometric properties of these clinical tools and their use in measuring intervention outcomes with children with CP classified as GMFCS level IV or V was identified.…”
Section: Methodsmentioning
confidence: 99%
“…The represented clinical outputs include a continuous ACR-N score, joint space narrowing (JSN), and bone erosion score (BES), and are directly tied to reductions in the cellular infiltrate, rate of cartilage degradation, and rate of bone degradation, respectively. An expanded discussion of relevant modeling methodology for autoimmune disorders has been given previously [20]. …”
Section: Methodsmentioning
confidence: 99%